Probing membrane protein-lipid interactions - Agasid, MT; Robinson, CV (Elsevier, 2021)
Structure determination of membrane proteins has highlighted the many roles played by lipids in influencing overall protein architecture. It is now widely accepted that lipids surrounding membrane proteins play crucial roles by modulating their conformational, structural, and functional properties. Capturing often transient lipid interactions and defining their chemical identity, however, remains challenging. Recent advances in mass spectrometry have resolved questions concerning lipid interactions by providing the molecular composition of intact complexes in association with lipids. Together with other biophysical tools, a picture is emerging of the dynamic nature of lipid-mediated interactions and their effects on conformation, interactions, and signaling.